Village Tourism: From Vector for Local Sustainable Development to Victim of its Own Success - Marotta, Ilaria; Monaco, Salvatore; Novelli, Marina (Fuori Luogo Journal of Sociology of Territory, Tourism, Technology, 2024)
Introduction special issue Villages